A study on the outcome of patients with down syndrome with congenital heart disease / Hasliza A Razak - Hasliza, A Razak (2017)
Backgrounds: Congenital heart defect (CHD) is the most common defect associated with Down syndrome (DS). Studies conducted in Asian countries reported ventricular septal (VSD) instead of atrioventricular septal defect (AVSD) as the most common congenital heart defect among Asian children with Down Syndrom. Objectives: To study the outcome of children with DS and t identify the distribution of CHD types in DS and the risk factors associated with poor outcome among patients with DS and CHD. Method: A retrospective, observational, cohort study conducted at two tertiary centres; University Malaya Medical Centre (UMMC) and Hospital Sultanah Aminah Johor Bahru (HSAJB) between 1st January 2005 to 31st December 2015 in children who are clinically diagnosed with DS. Patients from UMMC were identified from the Paediatric Cardiology and Genetic database in UMMC and patients from HSAJB are selected from Paediatric Cardiology Clinical Information System (PCCIS) and Jabatan Pendaftaran Negeri Johor. Medical records were reviewed for demographics, clinical characteristics, a sociated medical condition, 2D-echocardiography and chromosomal results. Parents were also contacted via phone call to gather missing information. Results: A total of 754 patients with DS were included in the study whereby 634 from HSAJB and 120 from UMMC. 420 (55.7%) patients had CHD and 334 (44%) had normal heart. Most common CHD was VSD in 138 (32.9%) followed by patent ductus arteriosus (PDA) in 125 (29.8%) and AVSD in 77 (18.4%). A total of 207 (40.9%) patients with CHD required surgical treatment. There were total of 131 (17 .5%) deaths in which, 95 (29%) patients with HD compared to 10.8% (36) patients without CHD died. A total of Ill 38 (40%) patients died prior to surgery with reducing trend in the number from 2013 to 2015. Fifteen patients (16%) died after surgery. The number of patients who died after surgery was relatively low with less than 5 patients each year. Highe t mortality was in AVSD patients (n=34, 44%) and 20 of them were treated conservatively. Survival probabilities for patients with CHD wa 79% up to 1 year of age and 75% up to 1O years. AVSD has the poorest survival outcome when compared to other CHD type , with only 60% survived to 1 year and 54% to 10 years. There were 2 significant factors that are associated with death for the patient with DS and CHD. Patients with severe CHD had a 3.117 higher likelihood to die compared to the mild and moderate patients (95% CI 1.741- 5.581, p<0.001). The presence of primary persistent pulmonary hypertension is also poor survival indicator (OR: 2.606, 95% CI 1.452-4.677). Conclusion: The prevalence of CHD in DS was 56% in this study, highlighting the importance of cardiac screening for children with DS. VSD is the commonest CHD followed by PDA and A VSD. The severity of the CHD and the presence of PPHN carries poor prognosis for the survival of the children with DS. It is important to refer children with DS and CHD for early surgery before pulmonary hypertension occurs.